Analyse og modellering af cyklisters nær-ulykker ved hjælp af storskala sensordata: Udvidet resumé - Chou, Kuan-Yeh; Rasmussen , Thomas; Jensen, Anders Fjendbo; Janstrup, Kira; Paulsen, Mads; Nielsen, Otto Anker (Proceedings from the Annual Transport Conference at Aalborg University, 2023)
To create safe cycling environments, it is important to reveal and gain detailed insights into potential accident-prone locations. While numerous studies have found that bicycle near accidents can be a surrogate measure to disclose risky places, few studies have explored near accidents using sufficient data sources with complete exposure levels and over extended periods of time. Using both crowdsourced near-accident data and conventional accident data (Police data), this study models and compares rates of accidents and near accidents in terms of infrastructure features in the Copenhagen area. Data covers 2019-2021, and results reveal that near accidents occur more frequently on pedestrian-oriented paths, while accidents tend to occur more frequently at intersections and roundabouts.